WUJUD BUDAYA DALAM NOVEL TEGUH ANAK JADAH KARYA A.D. DONGGO (KAJIAN ANTROPOLOGI SASTRA) - Amiruddin Amiruddin (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2019)
This research-oriented culture and a form of resistance against the culture of power in the novel Teguh Anak Jadah by A.D. Donggo studied from anthropological literature review. Interdisciplinary between anthropology and literature provide new understanding of the phenomenon of human culture in literature. The method used in this study using hermeneutic methods. This method outlined understand the text and the text intended for a review of literature. Hermeneutical suitable for reading literature for the study of literature, whatever its form, related to an activity that interpretation. In general, the study found a form of culture and a form of resistance against the culture of power in the novel Teguh Anak Jadah by A.D. Donggo. Cultural manifestation in the form of a value system, a system of norms, physical culture, specific rules, politics cultural activities, and the work. Novel Teguh Anak Jadah by A.D. Donggo It also shows the impact of the New Order regime and its cronies make public mindset when it becomes depressed, silent habit deeply ingrained during the New Order government has given rise to a new habit that is easy to forget. Forgetting the role of self, the role of the organization, the role of the family, against fellow citizens of different ideologies.